Clinical Evaluation of Surgical Procedures for Corneal Ulcer in Dogs - Pandey, Priyanka; Shahi, A.; Kumar, D.; Shukla , M.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was conducted on 12 dogs, irrespective of age sex and breed, having corneal ulcer to evaluate the response of surgical procedures. The animals were randomly divided into two groups, in group I temporary tarsorrhaphy and in group II third eyelid flap surgery was performed along with pre and post-operative systemic and local medication. Preoperative ophthalmoscopic examination was performed before starting the treatment, i.e. day 0, to check the general health status of the animals, followed by day 15, 30, 45 and 60 post-operative examination to record the healing of corneal ulcer. In group I lesser complications were observed as compared to group II and 66.66% and 50.00% dogs recovered without scar formation on 60th post-operative day in group I and II, respectively. Thus temporary tarsorrhaphy was observed superior then the third eyelid flap surgery as well as combination of moxifloxacin and flurbiprofen was found satisfactory for the healing of corneal ulcer.
Keywords: Dogs; Corneal ulcer; Temporary tarsorrhapy; Third eyelid flap surgery; Moxifloxacin